STRENGTHENING HUMAN RESOURCES CAPACITY AND CAPABILITY OF EMPLOYEES IN FACING CYBERLOAFING PHENOMENON - Chandra, Ade; Tibrani; Zamora, Ramon; Yona, Mira (Universitas Negeri Medan, 2024)
This study evaluates the direct and mediating relationships between work stress behavior and workload, with an emphasis on strengthening employee engagement to address the phenomenon of cyberloafing. The quantitative research involved a survey of 68 participants of varying ages and genders from the Batam City Transportation Agency. The relevance and impact of each indicator-variable influencing cyberloafing were tested using the structural equation model (SEM) based on partial least squares (PLS) through SmartPLS 4.1.03 software. The findings indicate that among the factors studied, two variables show a strong and significant positive correlation with cyberloafing (p-value = 0.000). Conversely, variables assessed through the median column reveal an insignificant effect with a positive but very weak correlation, ranging from 1% to 9%. These results suggest that enhancing employee capacity and capability alone is neither a primary nor a sufficient measure for the Batam City Transportation Agency to curb cyberloafing. The findings underscore that employee behavior can be influenced by complex workloads that contribute to work stress, impacting overall work performance. Thus, alternative approaches are needed to address the issue of cyberloafing, considering employee behavior on digital platforms in the modern era and its effect on job performance.